EFISIENSI DAN SDGs: PENGIMPLEMENTASIAN GREEN ACCOUNTING DAN MATERIAL FLOW COST ACCOUNTING - Rathu Rumbey Rochmalia; Ahmad Husin; Agus Triatmono (JURNAL ILMIAH EDUNOMIKA, 2026)
This research examines the influence of Green Accounting, Material Flow Cost Accounting (MFCA), and cost efficiency on the attainment of Sustainable Development Goals (SDGs) in manufacturing firms listed on the Indonesia Stock Exchange from 2022 to 2024. A quantitative methodology was employed, utilizing secondary data from annual and sustainability reports. Through purposive sampling, 41 firms were selected, resulting in 123 observations. Panel data regression using EViews 12 determined the Common Effect Model (CEM) as the most suitable estimation framework. The results indicate that neither Green Accounting nor Material Flow Cost Accounting (MFCA) significantly impacts the achievement of SDGs when tested individually. Conversely, cost efficiency demonstrates a positive and statistically significant influence on sustainable development performance. However, all three independent variables collectively exert a considerable effect on achieving the SDGs. These findings suggest that the effective management of costs and resource allocation plays a more crucial role in facilitating sustainable development than relying solely on separate environmental accounting methodologies. The originality of this research lies in the integration of Green Accounting, MFCA, and cost efficiency within a unified empirical model to elucidate sustainable development performance in the context of Indonesian manufacturing firms. Keywords : Green Accounting, Material Flow Cost Accounting (MFCA), Cost Efficiency, Sustainable Development, Manufacturing Companies